SYNTHESIS AND APPLICATION OF IONIC LIQUIDS AS CORROSION INHIBITOR FOR CARBON STEEL IN ACIDIC MEDIUM - RAMAN, NANTHINI (2019)
Carbon steel (CS) is the most commonly used material for machinery and pipelines by many industries, where it is exposed to corrosive environments. Aggressive Hydrochloric acid (HCl) is widely used due to its low cost and readily available. Acidic corrosion presents not only an economic loss but also an environmental and safety risk. Most industries use synthetic inhibitors, which are effective in reducing corrosion, but are also toxic, volatile and only available at high concentrations. This has led to the study of alternative inhibitors which can reduce this corrosion effect and at the same time being environmentally friendly